Aggregating particles on the O/W interface: Tuning Pickering emulsion for the enhanced drug delivery systems. Issue 2 (1st February 2022) - Ming, Yali; Xia, Yufei; Ma, Guanghui
Abstract: The rational design of drug delivery systems has led to enhanced targeting, increased efficiency, and a reduction of side effects in chemotherapies and vaccines. As most biological reactions took place at the interface, particle‐stabilized emulsion (Pickering emulsion), may offer major implications for the advanced drug loading, delivery, and controlled release. In fact, it is the aggregating particles that determined the multi‐level structure, multi‐valent cellular interactions, and the multi‐functional physiochemical properties in drug delivery. A deeper understanding on the tunable aggregating patterns and properties, as well as the underlying mechanisms, may pave the way for the efficient drug delivery, and also aided the progressing of "Aggregology" beyond molecules to particles, emulsions, and the biomedical applications. Here, the recent development of Pickering emulsions and their applications in drug delivery were thoroughly reviewed. Strategies to control over the physiochemical properties were illustrated based on particle properties, energy input, and the choices of continuous and dispersion phases. In particular, enough emphasis was attached on the structure‐effect relationship between the tunable physiochemical properties and the delivery process, such as the multi‐level structure for effective loading, flexibility and permeability for enhanced delivery, and the stimuli‐responsiveness for the controlled release. By channeling the unique interfacial properties and the enhanced drug delivery efficiency, this work may shed light on the rational design of Pickering emulsions for the efficient drug delivery. Abstract : Due to the fact that most biological reactions occur at the interface, particle‐stabilized emulsions (Pickering emulsions) may have major implications for the advanced loading, delivery, and controlled release of drugs. In fact, it is the aggregating particles that determine the multi‐level structure, multi‐valent cellular interactions, and the multifunctional physicochemical properties in drug delivery. The present article discusses recent developments in Pickering emulsions for drug delivery. By tuning the structures and physiochemical properties, Pickering emulsions could be used for stratifying the loading of multiple drugs, increasing the specific surface area for multivalent cellular interactions, and providing stimuli‐responsive particles for various biomedical applications. Furthermore, the structural effects in the multi‐scale drug delivery were also discussed, in regard to the strategies to target the specific tissue for high drug precision, provoke cellular internalization, and release in a controlled manner. Through the exploitation of the Pickering emulsion's unique interfacial properties and improved drug delivery efficiency, this study may provide insight into the rational design of Pickering emulsions for the efficient drug delivery.